Impact of free Fall Impact versus Treadmill Physical Exercise Programs: Which is Most Osteogenic? - PC, Aveline; E, Lespessailles; TM, Best; A, Cesaro; H, Toumi (Archives of Clinical and Medical Case Reports, 2022)
Exercise plays a key role for bone remodeling throughout our lives. Within bone cells, osteocytes have the ability to translate mechanical stimuli to bone anabolic cellular signaling. A variety of protocols have been used to apply both direct and indirect stimuli to bone. Herein, we compared running and free fall impact exercise protocols and their effects on markers of osteogenesis and bone strength. Methods: 50 female Wistar rats (6 weeks-old) were randomly assigned to either a sedentary group (S) or one of 4 exercise groups: treadmill training (T) and 3 Free-fall (F) groups (F30, F45, F60 respectively fall of 30, 45 and 60cm; 5 days/week, 8 weeks). We evaluated BMD and BMC (by DXA), bone microarchitecture of the left femur and tibia (by μCT), mechanical strength of the left femur (three-point bending test), and bone marker levels (by ELISA). Results: After 8 weeks of physical exercise (EXE), whole body BMD and BMC were both significantly higher from baseline in all EXE groups, with no difference between the 4 EXE groups. Left femur and tibia BMC and BMD significantly increased in the F45 and F60 groups compared to the S and T groups. BV/TV, Tb.Th and Tb.N were significantly higher in F45 and F60 compared to all other groups. Tb.N was significantly higher in F60 compared to F45. Yield point stress and Young modulus were significantly higher for F45 compared to S and T groups. Bone alkaline phosphatase and osteocalcin levels were significantly higher in the F45 group compared to the remaining groups. NTX level was significantly decreased in the F45 compared to the S and T groups. Conclusion: Both treadmill and impact training protocols produced a benefit on BMD and BMC. Interestingly, impact mechanical stress was a better stimulus for bone trabecular structure than treadmil